Mining the Biosynthetic Landscape of Lactic Acid Bacteria Unearths a New Family of RiPPs Assembled by a Novel Type of ThiF-like Adenylyltransferases - Wang, Mengjiao; Wu, Mengyue; Han, Meng; Niu, Xiaogang; Fan, Aili; Zhu, Shaozhou; Tong, Yigang (ACS omega, 2024)
Ribosomally synthesized and post-translationally modified peptides (RiPPs) are chemically diverse natural products of ribosomal origin. These peptides, which frequently act as signals or antimicrobials, are biosynthesized by conserved enzymatic machinery, making genome mining a powerful strategy for unearthing previously uncharacterized members of their class. Herein, we investigate the untapped biosynthetic potential of Lactobacillales (i.e., lactic acid bacteria), an order of Gram-positive bacteria closely associated with human life, including pathogenic species and industrially relevant fermenters of dairy products. Through genome mining methods, we systematically explored the distribution and diversity of ThiF-like adenylyltransferase-utilizing RiPP systems in lactic acid bacteria and identified a number of unprecedented biosynthetic gene clusters. In one of these clusters, we found a previously undescribed group of macrocyclic imide biosynthetic pathways containing multiple transporters that may be involved in a potential quorum sensing (QS) system. Through in vitro assays, we determined that one such adenylyltransferase specifically catalyzes the intracyclization of its precursor peptide through macrocyclic imide formation. Incubating the enzyme with various primary amines revealed that it could effectively amidate the C-terminus of the precursor peptide. This new transformation adds to the growing list of Nature’s peptide macrocyclization strategies and expands the impressive catalytic repertoire of the adenylyltransferase family. The diverse RiPP systems identified herein represent a vast, unexploited landscape for the discovery of a novel class of natural products and QS systems.